Child Sexual Abuse by Members of the Catholic Church in Italy and France: A Literature Review of the Last Two Decades. Issue 8 (17th November 2021) - Marotta, Giulia
ABSTRACT: This article aims to provide an overview of the most recent research on child sexual abuse by members of the Catholic Church that occurred in Italy and France. The studies reported here have been selected as representative of major trends in the field. In particular, they illustrate the paths taken by current scholarship addressing child sexual abuse that has occurred in mono-confessional Catholic culture areas not yet affected by large-scale scandals. The assessment of the last two decades of literature shows that existing research attests the presence of regional patterns regarding the incidence of confirmed cases of abuse, the cover–up procedures, and the reactions of both ecclesiastical and civil institutions and society. However, this review also indicates that scholars have thus far neglected to problematize the local peculiarities of the phenomenon, and to relate them to the broader debate on regional variability in the articulation of modernization processes and religious vitality and power.